Health Information: Applications and challenges in the COVID-19 pandemic - Sheree Lloyd; Sue M Walker; Ani Goswami (ACHSM, 2020)
Global health systems are under immense pressure with the exponential growth and spread of COVID-19.  Public health and health system responses to the pandemic have relied on health information reporting, visualisation, and projections of incidence, morbidity, and mortality. This commentary aims to explore how health information has been used to inform the public, manage risk, understand capacity, prepare the health system and to plan public health strategy.  We also aim to share the health information challenges and our insights to inform future debate and strategic investment.  This paper will be relevant to health service and health information managers wanting to understand vulnerabilities and focus for future health information initiatives.